Glioblastoma may evade immune surveillance through primary cilia-dependent signaling in an IL-6 dependent manner - Laws, Maxwell T.; Walker, Erin N.; Cozzi, Francesca M.; Ampie, Leonel; Jung, Mi-Yeon; Burton, Eric C.; Brown, Desmond A. (Frontiers in Oncology, 2023)
Glioblastoma is the most common, malignant primary brain tumor in adults and remains universally fatal. While immunotherapy has vastly improved the treatment of several solid cancers, efficacy in glioblastoma is limited. These challenges are due in part to the propensity of glioblastoma to recruit tumor-suppressive immune cells, which act in conjunction with tumor cells to create a pro-tumor immune microenvironment through secretion of several soluble factors. Glioblastoma-derived EVs induce myeloid-derived suppressor cells (MDSCs) and nonclassical monocytes (NCMs) from myeloid precursors leading to systemic and local immunosuppression. This process is mediated by IL-6 which contributes to the recruitment of tumor-associated macrophages of the M2 immunosuppressive subtype, which in turn, upregulates anti-inflammatory cytokines including IL-10 and TGF-β.Primary cilia are highly conserved organelles involved in signal transduction and play critical roles in glioblastoma proliferation, invasion, angiogenesis, and chemoradiation resistance. In this perspectives article, we provide preliminary evidence that primary cilia regulate intracellular release of IL-6. This ties primary cilia mechanistically to tumor-mediated immunosuppression in glioblastomas and potentially, in additional neoplasms which have a shared mechanism for cancer-mediated immunosuppression. We propose potentially testable hypotheses of the cellular mechanisms behind this finding.